Raise two effects with one scene: scene contexts have two separate effects in visual working memory of target faces - Tanabe-Ishibashi, Azumi; Ikeda, Takashi; Osaka, Naoyuki (Frontiers in Psychology, 2014)
Many people have experienced the inability to recognize a familiar face in a changed context, a phenomenon known as the “butcher-on-the-bus” effect. Whether this context effect is a facilitation of memory by old contexts or a disturbance of memory by novel contexts is of great debate. Here, we investigated how two types of contextual information associated with target faces influence the recognition performance of the faces using meaningful (scene) or meaningless (scrambled scene) backgrounds. The results showed two different effects of contexts: (1) disturbance on face recognition by changes of scene backgrounds and (2) weak facilitation of face recognition by the re-presentation of the same backgrounds, be it scene or scrambled. The results indicate that the facilitation and disturbance of context effects are actually caused by different two subcomponents of the background information: semantic information available from scene backgrounds and visual-array information commonly included in a scene and its scrambled picture. This view suggests visual working memory system can control such context information, so that it switches the way to deal with the contexts information; inhibiting it as a distracter or activating it as a cue for recognizing the current target.